Seasonal hydrologic responses to climate change based on a CMIP6 multi-model ensemble: A case study of An-Seong watershed in South Korea - Soyoung Woo; Wonjin Kim; Sun Woo Chang; Il-Moon Chung (Journal of Hydrology: Regional Studies)
Study region: The An-Seong watershed of South Korea. Study focus: This paper presents the impact of climate change on seasonal hydrologic responses using the SWAT model. The effects of climate change have been assessed through a multi-GCM ensemble approach, employing the Taylor skill score to minimize uncertainties of individual climate models. New hydrological insights for the region: Climate change significantly affected seasonal hydrological responses, primarily due to changes in precipitation and temperature. Future projections indicate an increase in precipitation across all seasons, with the most substantial rise during flood season (summer), marked by greater intensity. Temperature is expected to rise consistently across all seasons, and these changes have amplified hydrological responses, particularly during the dry season (winter). While precipitation increased during this period, the persistent rise of temperature led to elevated evapotranspiration regime. The analysis revealed a 10–20 % decline in groundwater recharge compared to historical conditions, highlighting an increased risk of winter drought and seawater intrusion in the An-Seong watershed. Proactive strategies designed to tackle these seasonal challenges are crucial for achieving sustainable water resource management as climate change continues to impact the region.